1999
DOI: 10.1074/jbc.274.1.335
|View full text |Cite
|
Sign up to set email alerts
|

The Carboxyl-terminal Region of Biliary Glycoprotein Controls Its Tyrosine Phosphorylation and Association with Protein-tyrosine Phosphatases SHP-1 and SHP-2 in Epithelial Cells

Abstract: Biliary glycoprotein (Bgp, C-CAM, or CD66a) is an immunoglobulin-like cell adhesion molecule and functions as a tumor suppressor protein. We have previously shown that the Bgp1 isoform responsible for inhibition of colonic, liver, prostate, and breast tumor cell growth contains within its cytoplasmic domain two tyrosine residues positioned in immunoreceptor tyrosine-based inhibition motif (ITIM) consensus sequences. Moreover, we determined that these residues, upon phosphorylation, associate with the protein-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
155
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(158 citation statements)
references
References 63 publications
3
155
0
Order By: Relevance
“…SHP-1 is known to bind to the cytoplasmic domain of CEACAM1-L upon tyrosine phosphorylation, thereby being activated [26]. Thus, our finding that CEACAM1 ligation in the granulocytes increased both CEACAM1 tyrosine phosphorylation and CEACAM1/SHP-1 association, suggests that SHP-1 activation is an upstream event in the Erk1/2 activation, leading to CEACAM1-induced delay of apoptosis.…”
Section: Discussionmentioning
confidence: 65%
“…SHP-1 is known to bind to the cytoplasmic domain of CEACAM1-L upon tyrosine phosphorylation, thereby being activated [26]. Thus, our finding that CEACAM1 ligation in the granulocytes increased both CEACAM1 tyrosine phosphorylation and CEACAM1/SHP-1 association, suggests that SHP-1 activation is an upstream event in the Erk1/2 activation, leading to CEACAM1-induced delay of apoptosis.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies concerning the role of CEACAM1 in epithelial cell cancers (47) and in an immortalized B cell line (31) have indicated that the SHP-1 and SHP-2 phosphatases can both associate with CEACAM1. Neisserial binding to CEACAM1 has been reported to suppress SHP-1 activity in monocytes (39).…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic domains of CEACAM1 are phosphorylated at their serine residues (Edlund et al, 1998;Fournes et al, 2001) and bind to calmodulin (Edlund et al, 1996). The CEACAM1-4L domain contains two tyrosine residues that recruit and activate pp60 c-src (Brummer et al, 1995) or the phosphatases SHP1 and -2 (Huber et al, 1999) upon phosphorylation. Signal transduction through the cytoplasmic domains appears to be important for the tumour suppressor function of CEACAM1 that has been initially suggested by clinical studies (Neumaier et al, 1993b;Nollau et al, 1997b) and subsequently by in vitro experiments and animal studies (Kunath et al, 1995;Obrink, 1997;Singer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%